Xexoxial Endarchy: Visual Poetry and Intentional Community at Dreamtime Village in the Midwestern United States - Lily Robert-Foley (IdeAs)
This paper examines a cross section of authors in the Xerolage collection, a subsection of the experimental poetry publisher Xexoxial Editions. Xerolage prints 25-page chapbooks of visual poetry using a Xerox machine. These chapbooks are printed in an intentional community in Lima, Wisconsin founded in 1991 by mIEKAL aND and Elisabeth Was called Dreamtime Village, that practices alternative living and permaculture farming. The paper asks what kind of link can be made between these practices of experimental writing, small press DIY printing, and alternative, resistant forms of social organization. The link between experimental writing and social/political resistance is a well-established one, particularly with regards to the avant-garde tradition. In this instance, however, readings of visual poets will be interwoven not just with political resistance but with logistical ones related to the practical matters of community building: housing, eating, living. We see that in both instances, the work challenges principles of order, as they pertain to both reading and civilization, and uses paragrammatic strategies of détournement, subverting this order by recycling, cutting, pasting and rearticulating how resistance can be drawn newly from forgotten pasts. The article examines the work of John M Bennet, David-Baptiste Chirot, Scott Helmes, Geof Huth, Andrew Topel, Elizabeth Was and mIEKAL aND.